The development and validation of the LIMPRINT methodology - Moffatt, Christine J.; Murray, Susie; Mercier, Gregoire; Quere, Isabelle; Franks, Peter (Mary Anne Liebert, 2017)
[Paper two of the LIMPRINT supplement. Lymphatic Research and Biology Supplement. June 2017]